Ryzyko - nowa kategoria bezpieczeństwa środowiskowego - Rak, Janusz; Tchórzewska-Cieślak, Barbara (Risk - a New Category of Environmental Safety, 2006)
In the work a new category of environmental safety, that is risk, has been presented. The three , four and five parametric matrix for risk assessment has been described in details. The size of risk is directly proportional to the probability that the threat occurs and to the magnitude of the negative consequences and inversely proportional to the degree of protection against threat.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 724-733